Can pharmacogenetics impact the therapeutic effect of cytarabine and anthracyclines in adult acute myeloid leukaemia patients? A Serbian experience - Pravdic, Zlatko; Virijević, Marijana; Mitrović, Mirjana; Pantić, Nikola; Sabljić, Nikica; Pavlović, Đorđe; Marjanović, Irena; Bukumirić, Zoran; Vidović, Ana; Jaković, Ljubomir; Pavlović, Sonja; Suvajdžić, Nada; et al. (Journal of Medical Biochemistry, 2024)
Background. Cytarabine-anthracycline based induction chemotherapy remains the standard of care for remission induction among patients with newly diagnosed acute myeloid leukaemia (AML). There are remarkable differences in therapy response among AML patients. This fact could be partly explained by the patients’ genetic variability related to metabolic paths of cytarabine and anthracyclines. The aim of this study is to evaluate the effect of variants in pharmacogenes SLC29A1, DCK, ABCB1, GSTM1 and GSTT1, as well as laboratory and AML-related parameters on clinical outcome in adult AML patients. Methods. A total of 100 AML patients were included in the study. Pharmacogenetic variants SLC29A1 rs9394992, DCK rs12648166, ABCB1 rs2032582 and GSTM1 and GSTT1 gene deletions were detected by methodology based on PCR, fragment analysis and direct sequencing. The methods of descriptive and analytic statistics were used. Survival analysis was done by the Kaplan-Meier method using the Log-Rank test.Results. This is the first study of adult AML pharmacogenetics in Serbian population. Clinical outcomes in our cohort of AML patients were not impacted by analysed variants in SLC29A1, DCK, ABCB1and GSTT1 and GSTM1 genes, independently or in combinations. Achievement of complete remission was identified as an independent prognostic indicator of clinical outcome.Conclusions. The population specific genomic profile has to be considered in pharmacogenetics. Since the data on AML pharmacogenetics in European populations is limited, our results contribute to knowledge in this field and strongly indicate that high-throughput approach has to be applied in order to find particular pharmacogenetic markers of AML in European population.
Keywords: AML; Anthracyclines; Cytarabine; Pharmacogenetic variants